Slægtens spor. Enok Mortensen: The danish Lutheran Church in America - Knudsen, Johannes (Grundtvig-Studier, 1969)
Enok Mortensen, The Danish Lutheran Church in America (Philadelphia 1967. - Board of Publications, Lutheran Church in America, and Kirkehistoriske Studier, ed. by. Institut for dansk Kirkehistorie) Reviewed by Johannes Knudsen. The history of the emigration offers a particularly favourable basis for a study of the development of Grundtvig’s thoughts. Although Danish emigrants in North America in 1880— 1900 may have misunderstood and reinterpreted the Grundtvigian Church and Folk High-School heritage, their work was nevertheless characterized by a healthy primitiveness, forgotten and distorted in modern Denmark. I should dislike having the emigrants placed in a procrustean bed similar to the one which has been made for Grundtvig. Denmark still clings to colonies of an ecclesiastical or national description beyond the borders of the country, with the result that they are prevented from growing into the communities of which they have now become parts. In many respects the ecclesiastical development in Denmark has stagnated in self-satisfaction, whereas work is continued in the rest of the world. There seems to be a connection between this dogmatism and the fact that historians have inquired into the conditions of the emigrants too unrealistically. In my opinion it was a tragic mistake when 40 years ago the emigrant archives were taken to Denmark— the more so as no research is taking place there. The review has a quotation from Franklin Clark Fry, the world-famed chairman of the Lutheran Church in America who wrote the preface to Enok Mortensen’s book, where, with reference to the descendants of the emigrants, it is said that “love of humanity is bred in the marrow of their bones”. More than anybody else the author of the present work has dealt with ecclesiastical history from the Grundtvigian side in America, and for many years he was the official historian and archivist of the Danish Church. A sum was set aside for the purposes of research and publication, and the book is the result of a comparatively thorough work of research. The fact is that it had to appear in print before it would lose some of its interest after the union of the American Evangelical Lutheran Church, and the author himself was in the sixties. Accordingly, much material is left for examination, and it is to be hoped that the job will be taken up by others of the next generation. The book will keep its title as the work about the Danish Church in America, however. The author has acquitted himself extremely well as regards the somewhat delicate task of selecting subjects and judging people and situations. His many years’ experience as a writer of novels and stories makes itself felt. His narrative skill makes the book both fascinating and readable. Especially the last exciting years have been dealt with in a true and moving manner, although with a note of sadness. A more extensive study is required, however, also with regard to our understanding of the development in Denmark. To read this book is to do oneself a favour. It gives a true, sober, but also warm-hearted picture of a century when the Danish Lutheran Church, especially in its Grundtvigian shape, was planted in North American soil, grew, flowered, and bore fruit. It does not live independently any longer, but like the grain of wheat which is put into the soil and capable of germinating.